2019
DOI: 10.3390/polym11040719
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Saltiness Perception Using Chitin Nanomaterials

Abstract: In the present study, we prepared and characterized chitin nanomaterials with different diameters, lengths, and degree of deacetylation (DD), and investigated their capability for enhancing saltiness perception. Chitin was isolated from squid pens and transformed into chitin nanofiber (CNF), deacetylated chitin nanofiber (DACNF), and chitin nanocrystal (CNC) by ultrasonication, alkali treatment followed by ultrasonication and acid hydrolysis, respectively. The diameters of CNF, CNC and DACNF were 17.24 nm, 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…This was substantiated by the study of Tsai et al . (2019) who reported that DD (22.89%) of chitin nanofibre (ultrasonicated at 20 kHz and 500W for 2 h) was not different from that (22.84%) of the control chitin (not ultrasonicated). In another study, DD of β‐chitin was 23%, 22%, 22% and 21% after ultrasonication for 0, 30, 45 and 60 min (Jiang et al ., 2017).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This was substantiated by the study of Tsai et al . (2019) who reported that DD (22.89%) of chitin nanofibre (ultrasonicated at 20 kHz and 500W for 2 h) was not different from that (22.84%) of the control chitin (not ultrasonicated). In another study, DD of β‐chitin was 23%, 22%, 22% and 21% after ultrasonication for 0, 30, 45 and 60 min (Jiang et al ., 2017).…”
Section: Resultsmentioning
confidence: 97%
“…The insignificant changes in DD observed by Jiang et al ., (2017) and Tsai et al . (2019) were likely due to the low ultrasonication power. Jiang et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright (2007) American Chemical Society. ( f ) TEM micrograph of chitin nanofibers, reprinted with permission from [ 46 ]. ( g ) Repeating unit of starch.…”
Section: Figurementioning
confidence: 99%